MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA KELAS VII PADA OPERASI HITUNG BILANGAN BULAT MELALUI MEDIA GARIS BILANGAN “MOBILBUT” - Mellinda, Cinta; Putri, Agustiany Dumeva; Efriani, Arvin (INSPIRAMATIKA, 2025)
The background of this is due to the low understanding of mathematical concepts in the material of addition and subtraction operations of whole numbers in class VII MTs Hidayatul Islamiyah, this is due to the lack of student learning motivation. Therefore, this study aims to increase students' motivation and interest in learning through the application of MOBILBUT number line media in learning mathematics. This research was conducted offline in the even semester of the 2024/2025 school year, involving 11 students of class VII MTs Hidayatul Islamiyah. The research method used in this article is to use a descriptive qualitative approach, with data collection techniques including observation, interviews, questionnaires, and learning documentation. The results showed that MOBILBUT is effective and easy to use, encourages active student participation, and increases student motivation and interest in learning. This can be seen from the observation results which show an increase in students' active participation during learning. Students reported increased learning motivation in interviews, with some students stating that MOBILBUT made learning math more interesting and easy to understand.